CRISIS MANAGEMENT STRATEGY IN ISLAMIC EDUCATIONAL INSTITUTIONS AT MADRASAH IBTIDAIYAH MUARA RUPIT, RUPIT DISTRICT, MURATARA REGENCY - Kartika, Mirna; Zainuri, Ahmad; Maryamah, Maryamah (Jurnal Konseling Pendidikan Islam, 2026)
Internal management crises represent a critical challenge for Islamic educational institutions, particularly at the elementary level such as madrasah ibtidaiyah. Issues including internal conflicts, weak organizational coordination, and high teacher turnover may significantly affect institutional stability and the quality of educational services. This study aims to analyze the crisis management strategies implemented by Madrasah Ibtidaiyah Muara Rupit, Rupit District, North Musi Rawas Regency (Muratara), in addressing internal management crises. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with the head of the madrasah, teachers, and administrative staff, participatory observation of institutional activities, and document analysis of organizational policies and records. Data analysis was conducted using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal that crisis management strategies at Madrasah Ibtidaiyah Muara Rupit are implemented through three main stages: internal crisis identification, strengthening organizational communication, and management restructuring grounded in Islamic values. The head of the madrasah plays a pivotal role as a key actor in managing crisis communication in a persuasive and participatory manner to mitigate conflicts and maintain internal trust. These findings underscore that effective crisis management in Islamic educational institutions is strongly influenced by adaptive leadership, open organizational communication, and the integration of religious values in decision-making processes. This study is expected to contribute both theoretically and practically to the development of crisis management practices in Islamic elementary education institutions.